Culture - Theory - Disability Encounters between Disability Studies and Cultural Studies - Waldschmidt, Anne; Berressem, Hanjo; Ingwersen, Moritz (Disability Studies. Körper - Macht - Differenz, 2017)
Which theoretical approaches of contemporary cultural criticism can Disability Studies employ? At the same time, what can Cultural Studies gain by incorporating disability more fully as a framework for critical analysis? This international collection of essays enriches the thriving discourse of Cultural Disability Studies by offering stimulating dialogues between British, Czech, German and US-American scholars. In order to contour the various 'contact zones' between the two fields, the volume works transdisciplinarily, drawing on fields such as sociology, literary studies, art history and philosophy.